Digital Marketing Tools or e-WOM? Tourists Motivation to Enjoy the Charm of Blue Fire on Ijen Crater Ecotourism - SURYANINGSIH, Ika Barokah; WULANDARI, Gusti Ayu; NUGRAHA, Kristian Suhartadi Widi; PARAMITA, Cempaka; YURI, Queen Islam Brilliant (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
The most significant contributor to foreign exchange in Indonesia besides oil and gas is tourism. One of the regencies in Indonesia that has tourism potential is the Banyuwangi Regency. Almost all regions in Banyuwangi have beautiful natural charm in the form of mountains, beaches and forests. The existence of cultural diversity and traditional customs also makes Banyuwangi as a potential district in terms of tourism. This research was conducted in the Ijen Crater tour because it is a natural tourist destination that is most sought after and attractive to potential tourists. In 2016, 30% of foreign tourists visiting Banyuwangi visited Ijen Crater. At this time, most of the world community can not be separated from the use of social media. Therefore, the application of digital marketing and the selection of the right digital marketing tools can increase the number of tourist visits. Management of digital marketing and selection of useful digital marketing tools will form a positive Word of mouth (WOM). When WOM is positive, it is possible to increase the motivation of tourists to visit.